Design and Implementation of a Wireless Transmission Signal Simulation System Based on STM32 - Liu, Kechi; Li, Wei; Gao, Zhengjie; Zheng, Tao (International Journal of Advanced AI Applications, 2025)
Targeting the characteristics of line-of-sight and multipath signal propagation in wireless communication systems, a wireless transmission signal simulation system was designed and implemented. The system uses the STM32F103RCT6 microcontroller as the core, controlling the AD9959 quad-channel Direct Digital Synthesizer (DDS) via the SPI interface to generate multi-channel radio frequency baseband signals. An AD8367 variable gain amplifier is used for precise adjustment of signal amplitude. An AD835 four-quadrant analog multiplier is utilized for signal mixing and multipath synthesis. Through a filtering circuit to filter out sampling distortion, finally, the line-of-sight signal and delayed multipath components are additively synthesized to obtain the simulated wireless transmission signal. Experimental results show that this system can stably generate multi-channel signals with adjustable amplitude and phase, and the output error meets the design specifications, providing an effective tool for wireless channel simulation and communication testing.